Parenting and sharenting communication for preventing juvenile delinquency - Suranto Aw; Pratiwi Wahyu Widiarti; Benni Setiawan; Normah Mustaffa; Mohd Nor Shahizan Ali; Chatia Hastasari (Informasi, 2020)
The focus of this research is to examine the communication techniques between parents and children in the context of parenting and giving advice (sharenting) for the prevention of children or adolescents' delinquency. The informants of this research were students, teachers, parents, and community leaders from two countries (Indonesia and Malaysia). Data were collected utilizing the focus group discussion techniques via Zoom meeting platform. Data were analyzed using interactive analysis which includes four stages, namely: data collection, data reduction, display data, and drawing a conclusion/verification. The results show that parenting and sharenting communication are strategic forums to guide adolescents to avoid various forms of deviant behavior, especially delinquency. The communication techniques applied consist of persuasive and in certain conditions coercive communication techniques are utilized. Communication barriers include the lack of commitment of some parents in carrying out comprehensive communication.